229. The Role of Antimicrobial Stewardship Program on Appropriate Use, Dose, and Duration of Vancomycin Treatment. (26th November 2018) - Kaplun, Olga; Monteforte, Melinda; Tirmizi, Samad; Abate, Mersema; Psevdos, George; Go, Roderick
Abstract: Background: In an era of increasing bacterial resistance, antimicrobial stewardship programs (ASP) are essential in guiding judicious antibiotic use and improving patient safety goals. A prior medication use evaluation of vancomycin conducted at Stony Brook University Hospital (SBUH) identified three areas for improvement: (1) vancomycin dosing to achieve target trough concentration, (2) treatment duration, (3) and the use of vancomycin drug assay. As a result, the ASP at SBUH implemented an interdisciplinary team which consists of pharmacists and physicians to optimize these areas. Methods: A prospective quality improvement program was implemented from October 1, 2017 to December 31, 2017. Patients on two medicine units (60 patient beds) were enrolled in the program if they received vancomycin for more than one day and were not on hemodialysis. The ASP monitored for appropriate use of vancomycin as well as providing real-time guidance on dosing and serum concentration monitoring. If vancomycin was not indicated or de-escalation was warranted, the physician was contacted for discontinuation or de-escalation. To evaluate the impact of the program, we selected comparable patients from two other medicine units during the same period as the control group. Duration of vancomycin therapy, the percentage of patients achieving target trough level and 24-hour AUC within 72 hours, and use of vancomycin drug assay were compared. Results: There were 84 patients in the intervention group and 142 patients in the control group with similar age, weight, and creatinine clearance. The intervention group achieved a 20% reduction in the days of vancomycin use (median days of therapy 4.55 vs. 5.7 days, P = 0.071), a higher percentage of patient achieving trough level of 10–20 μg/mL (80.65% vs. 51.79%, P = 0.0001) and 24 hour AUC >400 mg hours/L (95.16% vs. 74.6%, P = 0.001), and a lower number of trough levels per course (1.51 vs. 2.54, P = 0.007). The 3-month medication cost savings from the program on these two units was over $6, 000. Conclusion: An ASP supervised program led to a reduction in vancomycin days of therapy, early attainment of optimal exposure, and decreased use of laboratory resources. Moreover, the program lowered the overall healthcare cost. Disclosures: All authors: No reported disclosures.